Method for processing large-aspect-ratio titania nano-pattern on silver substrate

CN115535957BActive Publication Date: 2026-10-23WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211183715.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2026-10-23
Estimated Expiration
2042-09-27

AI Technical Summary

Benefits of technology

[0026]本发明克服了目前制备反射型超构透镜存在的基底银层不平整的工艺问题,通过采用铝和铬双金属层为硬掩模的方法,可以在银基底上制备高深宽比二氧化钛,不仅实现了二氧化钛纳米图案的深宽比大于30,且保证了基底银层厚度均匀平整,可用于宽带、广角、高效平面超表面聚光器的制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115535957B_ABST
    Figure CN115535957B_ABST
Patent Text Reader

Abstract

The application discloses a processing method of a large-aspect-ratio titanium dioxide nano pattern on a silver substrate, and comprises the following steps: taking an aluminum-chromium bimetallic layer as a hard mask to etch a titanium dioxide nano pattern on a substrate plated with a silver and titanium dioxide double-layer film, and then removing the residual aluminum mask by using an aluminum etching solution without damaging the silver film substrate with uniform and flat thickness. The application realizes the large aspect ratio of the titanium dioxide nano pattern, and ensures the uniform and flat thickness of the silver layer, and can be used for the preparation of a broadband, wide-angle and high-efficiency planar metasurface condenser.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor micro-nano fabrication technology, and more specifically to a method for fabricating titanium dioxide nanopatterns with a large aspect ratio on a silver substrate. Background Technology

[0002] Based on their interaction with light waves, current metasurfaces or metalenses can be classified into transmissive and reflective types. Currently, transmissive metasurfaces or metalenses, due to their mature fabrication technology, have gradually been commercialized in highly integrated optical systems, with various functional devices emerging in the visible, infrared, terahertz, and microwave frequency bands. Reflective optical metasurfaces or metalenses, however, are limited by fabrication technology, and few have been realized to date. Literature reports often only demonstrate simulations using three-dimensional electromagnetic field simulation software (CST) or the finite-difference time-domain method (FDTD), especially lacking physical verification in the visible light band. Compared to transmissive structures, reflective structures, due to the presence of a metal backplate, have a natural advantage in achieving full phase coverage from 0 to 2π. If current fabrication limitations can be overcome, it will drive their application in optical devices such as surface plasmon couplers, polarization converters, optical holography, and solar thermal collectors.

[0003] Reflective metasurfaces or metalenses are mainly divided into two categories: one type is based on plasma resonance and uses a three-layer "metal-dielectric-metal" structure to achieve phase modulation of reflection. Its characteristic is a small structural thickness (reaching the depth subwavelength scale). However, considering the inherent ohmic loss of metal in the visible light band, the efficiency of field control for this type of metasurface or metalens is often very low; for metalenses, the focusing efficiency is generally only 10%-20%. Furthermore, this type of design has low tolerance for processing precision, which is not conducive to practical applications. The other type uses a "dielectric-metal" structure, utilizing either the transmission phase, the structural phase, or both simultaneously to achieve full-phase modulation. Due to the large band gap of the dielectric material, it has low absorption in the visible light band, which helps to achieve efficient utilization of light waves.

[0004] Currently, for visible light bandgap "dielectric-metal" metasurfaces or metalenses, considering the dielectric material's large indirect bandgap (achieving low absorption), high refractive index, and chemical stability, titanium dioxide is the top choice among many materials. Meanwhile, considering silver's reflectivity of over 95% in the visible light band, it is the optimal choice for a metal backing plate.

[0005] To create the desired high aspect ratio structural patterns from titanium dioxide, an etching process is required. However, traditional etching processes using metal as a hard mask for titanium dioxide etching suffer from problems such as a low etching selectivity (the etching selectivity ratio of chromium to titanium dioxide is about 4:1, and that of aluminum to titanium dioxide is about 2:1) and a small tilt angle of the titanium dioxide unit structure.

[0006] In the fabrication of transmissive metasurfaces or metalenses, the aforementioned problems have been effectively alleviated through process improvements. For example, patent CN110347014A discloses a vertical etching process for fabricating high aspect ratio titanium dioxide. The etching method involves optimizing the etching process when etching titanium dioxide using a metal hard mask, achieving an etching rate of 10 nm / min for titanium dioxide and 0.095 nm / min for the metal mask. The selectivity can theoretically reach 105, making it perfectly suitable for etching high aspect ratio titanium dioxide structures.

[0007] However, the above methods cannot be directly applied to the fabrication of "dielectric-metal" type reflective metasurfaces or metalenses. This is because using metal as a hard mask for etching to fabricate reflective metasurfaces or metalenses in the visible light band faces two main problems: First, when using chromium as a hard mask, although theoretically a large aspect ratio can be achieved by optimizing the etching process, if the chromium layer is too thin, it is impossible to etch the desired titanium dioxide structure. If the chromium layer is too thick, physical or chemical methods are required to remove the residual chromium. In this process (if physical methods are used, continuing etching while removing the residual chromium layer will damage the silver layer; if chemical methods are used to remove the residual chromium layer, the chromium etching solution (usually cerium ammonium nitrate solution) will react with the silver layer), the original uniform and flat silver surface will be irreversibly damaged, reducing its reflectivity and thus affecting the working efficiency of the reflective metasurface or metalens. Second, when using aluminum as a hard mask, although the aluminum etching solution will not corrode the silver, the etching selectivity of aluminum and titanium dioxide is relatively small, which is not conducive to achieving reflective metalenses with good focusing in the visible light band. Summary of the Invention

[0008] The technical problem to be solved by the present invention is to provide a method for processing titanium dioxide nanopatterns with a large aspect ratio on a silver substrate, which addresses the above-mentioned defects in the prior art. This method achieves a large aspect ratio of titanium dioxide nanopatterns while ensuring that the thickness of the silver layer on the substrate is uniform and flat.

[0009] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows:

[0010] A method for fabricating high aspect ratio titanium dioxide nanopatterns on a silver substrate includes the following steps:

[0011] Step 1: After uniformly spin-coating a layer of photoresist on the surface of a double-layer film with a silver film layer and a titanium dioxide layer deposited sequentially on the sample substrate, a photoresist pattern complementary to the desired titanium dioxide nanopattern is constructed by electron beam exposure.

[0012] Step 2: In sequence, an aluminum film with a thickness of H4 and a chromium film with a thickness of H5 are deposited, and the remaining photoresist is removed with a stripping solution to obtain a nanopattern with an aluminum-chromium double metal mask on the surface of titanium dioxide.

[0013] Step 3: Use an ion beam to vertically etch the titanium dioxide layer until the underlying silver film layer is exposed. At this point, only the titanium dioxide layer with a metal aluminum mask remains on the surface after partial etching.

[0014] Step 4: Use aluminum etching solution to remove the residual aluminum mask on the surface of the titanium dioxide layer to prepare a titanium dioxide nanopatterned metasurface with a large aspect ratio based on silver.

[0015] According to the above technical solution, in step 3, an etchant is used in the etching process of the titanium dioxide layer with aluminum-chromium double metal mask. The thickness H5 of the chromium film layer is slightly less than or equal to the product of the selectivity ratio S2 of the etchant for chromium and titanium dioxide and the thickness H1 of the titanium dioxide layer.

[0016] The thickness of the photoresist, H3, is more than 2-3 times the sum of the thickness of the chromium layer mask, H5, and the thickness of the aluminum layer mask, H4.

[0017] According to the above technical solution, the photoresist is either PMMA photoresist or negative photoresist, with PMMA photoresist showing the best performance. To achieve a structure of tens of nanometers, the PMMA photoresist thickness should be as thin as possible. Furthermore, to facilitate the subsequent stripping process, the thickness H3 can be controlled between 100-200 nm. In step 4, the aluminum etching solution is a mixed acid solution.

[0018] According to the above technical solution, in step 1, the specific process of uniformly spin-coating a layer of photoresist on the surface of the double-layer film with a silver film layer and a titanium dioxide layer deposited on the substrate surface is as follows: first, silver is sputtered by a magnetron sputtering stage to form a silver film layer of a certain thickness on the substrate surface; then, titanium dioxide is deposited by electron beam evaporation by a vacuum coating machine to deposit a titanium dioxide layer of a certain thickness on the silver film layer; then, it is uniformly spin-coated onto the titanium dioxide layer by a spin coater. After the spin coat is completed, the sample is placed on a drying stage for pre-drying.

[0019] According to the above technical solution, in step 1, the specific process of constructing a photoresist pattern complementary to the desired titanium dioxide nanopattern by electron beam exposure is as follows: using electron beam exposure technology, a high-energy electron beam is bombarded on the sample surface. The electron beam scans according to the inverse structure of the set pattern, causing the photoresist of the inverse structure pattern to denature and thus solidify. Then, the undenatured and uncured photoresist is removed by developing solution, exposing the underlying titanium dioxide layer in the uncured photoresist areas.

[0020] According to the above technical solution, in step 2, an aluminum film of a certain thickness and a chromium film of a certain thickness are sequentially deposited, and the remaining photoresist is removed with a stripping solution to obtain a nanopattern with an aluminum-chromium double-layer metal mask on the surface of titanium dioxide. The specific process is as follows: aluminum and chromium are sputtered by a magnetron sputtering instrument to sequentially form an aluminum film of thickness H4 and a chromium film of thickness H5 on the sample surface. Then, the photoresist that has been cured on the sample is removed with a stripping solution to obtain a nanopattern with an aluminum-chromium double-layer metal mask on the surface of titanium dioxide.

[0021] According to the above technical solution, in step 2, after the photoresist is removed by the stripping solution, the photoresist is further removed and stripped by a pneumatic gun containing acetone.

[0022] According to the above technical solution, in step 3, the titanium dioxide layer is vertically etched with an ion beam until the underlying silver film layer is exposed. At this time, only the titanium dioxide layer with a metal aluminum mask remains on the surface after partial etching. The specific process is as follows: First, the nanopattern is transferred to the titanium dioxide layer by reactive ion etching. During the etching process, an etchant composed of SF6, CHF3 and O2 gas is used to etch chromium. Then, a plasma etching machine is used to etch titanium dioxide with aluminum as a hard mask, and an etchant composed of CCl4 and O2 gas is introduced during the process.

[0023] According to the above technical solution, the aspect ratio of titanium dioxide nanopatterns can reach 20:1, or even more than 30:1. The aspect ratio of titanium dioxide nanopillars refers to the ratio of the height of the titanium dioxide nanopillars to the minimum feature size. The angle between the side face of the titanium dioxide nanopillars, the structural unit in the prepared titanium dioxide nanopatterns, and the horizontal plane is between 80° and 90°.

[0024] According to the above technical solution, in step 4, the aspect ratio of the nanopattern is greater than 30, and the nanopattern is a reflective metasurface or metalens with light-gathering properties.

[0025] The present invention has the following beneficial effects:

[0026] This invention overcomes the problem of uneven silver substrate in current reflective metalenses. By using an aluminum and chromium bimetallic layer as a hard mask, high aspect ratio titanium dioxide can be prepared on a silver substrate. This not only achieves an aspect ratio greater than 30 for the titanium dioxide nanopatterns, but also ensures that the silver substrate has a uniform and flat thickness. It can be used to prepare broadband, wide-angle, and high-efficiency planar metasurface concentrators. Attached Figure Description

[0027] Figure 1 This is a schematic diagram illustrating the changes in a sample during the implementation of the processing method for high aspect ratio titanium dioxide nanopatterns on a silver substrate in an embodiment of the present invention.

[0028] Figure 2 This is a schematic diagram of a sample in an embodiment of the present invention in which a layer of PMMA photoresist is spin-coated onto the surface of a double-layer film of silver and titanium dioxide.

[0029] Figure 3 This is a schematic diagram of a sample in an embodiment of the present invention, in which a PMMA photoresist pattern complementary to the desired titanium dioxide nanopattern is constructed by electron beam exposure.

[0030] Figure 4 This is a schematic diagram of a sample coated with an aluminum-chromium double-layer metal mask in an embodiment of the present invention;

[0031] Figure 5 This is a schematic diagram of the sample after the PMMA photoresist has been removed in an embodiment of the present invention;

[0032] Figure 6 This is a schematic diagram of a sample after etching the titanium dioxide layer until the underlying silver film layer is exposed, as described in an embodiment of the present invention.

[0033] Figure 7 This is a schematic diagram of the sample after etching in an embodiment of the present invention;

[0034] In the figure, 1-PMMA photoresist, 2-titanium dioxide layer, 3-silver film layer, 4-substrate, 5-chromium, 6-aluminum. Detailed Implementation

[0035] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0036] Reference Figure 1 As shown, a method for fabricating high aspect ratio titanium dioxide nanopatterns on a silver substrate according to one embodiment of the present invention includes the following steps:

[0037] Step 1: After uniformly spin-coating a layer of PMMA photoresist onto the surface of the sample substrate, which is sequentially coated with a double-layer film of silver and titanium dioxide, as shown... Figure 2As shown, a PMMA photoresist pattern complementary to the desired titanium dioxide nanopattern is constructed using electron beam lithography, such as... Figure 3 As shown;

[0038] Step 2: Sequentially deposit an aluminum film with a thickness of H4 and a chromium film with a thickness of H5, as follows: Figure 4 As shown, the remaining PMMA photoresist was removed with a stripping solution, resulting in a nanopattern with an aluminum-chromium double-layer metal mask on the titanium dioxide surface, as shown. Figure 5 As shown;

[0039] Step 3: Vertically etch the titanium dioxide layer using an ion beam until the underlying silver film is exposed. At this point, only a partially etched titanium dioxide layer with an aluminum mask remains on the surface. Figure 6 As shown;

[0040] Step 4: The residual aluminum mask on the surface of the titanium dioxide layer is removed using an aluminum etching solution to prepare a high aspect ratio titanium dioxide nanopatterned metasurface with a silver substrate, such as... Figure 7 As shown.

[0041] Furthermore, the PMMA photoresist is a polymethyl methacrylate photoresist.

[0042] Further, in step 1, the sequential deposition of a silver and titanium dioxide double-layer film on the substrate surface refers to the sequential deposition of a silver layer with a thickness of H2 and a titanium dioxide layer with a thickness of H1 on the substrate surface; PMMA photoresist is uniformly spin-coated onto the titanium dioxide layer, and the thickness of the PMMA photoresist is H3, with the structure as follows. Figure 2 As shown.

[0043] On a substrate with a silver and titanium dioxide double-layer film deposited on its surface, an aluminum-chromium bimetallic layer is used as a hard mask. After etching, the residual aluminum mask is removed with a mixed acid without damaging the silver film substrate with uniform thickness and flatness.

[0044] Furthermore, in step 3, an etchant is used in the etching process of the titanium dioxide layer with aluminum-chromium double metal mask. The thickness of the chromium film layer H5 is slightly less than or equal to the product of the selectivity ratio of the etchant to chromium and titanium dioxide S2 and the thickness of the titanium dioxide layer H1, so as to ensure that the chromium mask layer is completely consumed and a portion of the aluminum mask thickness is consumed when the titanium dioxide film is etched through.

[0045] The thickness of the PMMA photoresist, H3, is 2-3 times or more the sum of the thickness of the chromium layer mask, H5, and the thickness of the aluminum layer mask, H4.

[0046] Furthermore, the selectivity ratio of the etchant to aluminum to titanium dioxide S1 and the selectivity ratio of chromium to titanium dioxide S2 are both much greater than 1, especially S2.

[0047] Furthermore, in step 4, the aluminum etching solution is a mixed acid solution. The aluminum layer mask can facilitate the removal of residual metallic aluminum with the aluminum etching solution without corroding the silver film, thus ensuring that the constructed nanopattern has a uniform and flat silver film substrate layer.

[0048] A mixed acid solution was used, with a component ratio of phosphoric acid: hydrochloric acid: water = 3:1:12. The final result is as follows: Figure 7 The reflective meta-lens shown has several spaced titanium dioxide structural units formed on a silver-plated substrate. The height of the titanium dioxide is H1, and the cross-sectional shape is square.

[0049] Furthermore, the angle between the side face of the titanium dioxide nanopillar, the structural unit in the prepared titanium dioxide nanopattern, and the horizontal plane is between 80° and 90°.

[0050] Furthermore, in steps 1 and 2, the structure of the nanopattern can be designed according to its function, with an aspect ratio greater than 30. The nanopattern is a reflective metasurface or metalens with light-gathering properties, such as... Figure 1 As shown.

[0051] Further, in step 1, the specific process of uniformly spin-coating a layer of PMMA photoresist onto the surface of the substrate with a double-layer film of silver and titanium dioxide is as follows: first, silver is sputtered using a DE500 magnetron sputtering stage at a sputtering rate of... A silver film of a certain thickness is formed on the substrate surface; then, titanium dioxide is deposited by electron beam evaporation using an Ohmiker-50B vacuum coating machine, with a deposition rate of [missing information]. A titanium dioxide layer of a certain thickness is deposited on a silver film of a certain thickness; then it is uniformly spin-coated onto the titanium dioxide layer using a spin coater. After spin coating is completed, the sample is placed on a drying table and pre-dried at 60°C for 15 minutes.

[0052] Further, in step 1, the specific process of constructing a PMMA photoresist pattern complementary to the desired titanium dioxide nanopattern using electron beam exposure is as follows: Using electron beam exposure technology, a high-energy electron beam bombards the sample surface. Based on the GDS file containing information such as the sample size and period, stored via MATLAB, the electron beam scans according to the inverse structure of the pre-defined pattern, causing the PMMA photoresist of the inverse structure pattern to denature and solidify. Then, the undenatured and uncured PMMA photoresist is removed using a developer, exposing the underlying titanium dioxide layer, the structure of which is as follows: Figure 3 As shown.

[0053] Further, in step 2, an aluminum film of a certain thickness and a chromium film of a certain thickness are sequentially deposited, and the remaining PMMA photoresist is removed with a stripping solution. The specific process for obtaining a nanopattern with an aluminum-chromium double-layer metal mask on the titanium dioxide surface is as follows: Aluminum and chromium are magnetron sputtered using a LAB18 magnetron sputtering instrument at sputtering rates of... and An aluminum film of thickness H4 and a chromium film of thickness H5 were sequentially formed on the remaining sample surface. Then, the cured PMMA photoresist on the sample was removed using a stripping solution, resulting in a titanium dioxide surface as shown in the image. Figure 5 The nanoscale pattern shown is made with an aluminum-chromium double-layer metal mask;

[0054] Furthermore, in step 2, after removing the PMMA photoresist with the stripping solution, the PMMA photoresist is further removed and stripped using an air gun filled with acetone. First, the pressure of the acetone air gun must be adjusted. If the pressure is too high, it may blow away the microstructures on the sample surface; however, if the pressure is too low, it may leave photoresist residue on the sample surface. After adjusting the air pressure, the nozzle is tilted at 45° towards the sample for stripping.

[0055] Further, in step 3, the titanium dioxide layer is vertically etched using an ion beam until the underlying silver film layer is exposed. At this point, only the partially etched titanium dioxide layer with an aluminum mask remains on the surface. The specific process is as follows: First, the nanopattern is transferred onto the titanium dioxide layer using reactive ion etching in an Oxford 800Plus. During the etching process, an etchant composed of SF6, CHF3, and O2 gas is used to etch chromium, with SF6 and CHF3 introduced at a volume ratio of 5.5:1. O2 is added to accelerate the etching rate in the vertical direction. Then, a plasma etching machine is used to etch the titanium dioxide using aluminum as a hard mask, and an etchant composed of CCl4 and O2 gas is introduced during the process at a certain ratio. The final etching result is as follows. Figure 6 As shown.

[0056] The above are merely preferred embodiments of the present invention and should not be construed as limiting the scope of the present invention. Therefore, any equivalent changes made in accordance with the claims of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for fabricating high aspect ratio titanium dioxide nanopatterns on a silver substrate, characterized in that, Includes the following steps: Step 1: After uniformly spin-coating a layer of photoresist on the surface of a double-layer film with a silver film layer and a titanium dioxide layer deposited sequentially on the substrate surface, a photoresist pattern complementary to the desired titanium dioxide nanopattern is constructed by electron beam exposure. Step 2: In sequence, an aluminum film with a thickness of H4 and a chromium film with a thickness of H5 are deposited, and the remaining photoresist is removed with a stripping solution to obtain a nanopattern with an aluminum-chromium double metal mask on the surface of titanium dioxide. Step 3: Use an ion beam to vertically etch the titanium dioxide layer until the underlying silver film layer is exposed. At this point, only the titanium dioxide layer with a metal aluminum mask remains on the surface after partial etching. Step 4: Use aluminum etching solution to remove the residual aluminum mask on the surface of the titanium dioxide layer to prepare a titanium dioxide nanopatterned metasurface with a large aspect ratio based on silver. In step 3, an etchant was used during the etching process of the titanium dioxide layer with the aluminum-chromium double metal mask. The thickness of the chromium film layer H5 was slightly less than or equal to the product of the selectivity ratio of the etchant to chromium and titanium dioxide S2 and the thickness of the titanium dioxide layer H1, so as to ensure that the chromium mask layer was completely consumed and a portion of the thickness of the aluminum mask was consumed when the titanium dioxide film was etched through. The thickness of the photoresist, H3, is more than 2-3 times the sum of the thickness of the chromium layer mask, H5, and the thickness of the aluminum layer mask, H4. In step 2, aluminum films and chromium films of a certain thickness are deposited sequentially, and the remaining photoresist is removed with a stripping solution to obtain a nanopattern with an aluminum-chromium double-layer metal mask on the surface of titanium dioxide. The specific process is as follows: aluminum and chromium are sputtered by a magnetron sputtering instrument to form an aluminum film with a thickness of H4 and a chromium film with a thickness of H5 on the surface in sequence. Then, the photoresist that has been cured on the sample is removed with a stripping solution to obtain a nanopattern with an aluminum-chromium double-layer metal mask on the surface of titanium dioxide. In step 1, the specific process of constructing a PMMA photoresist pattern complementary to the desired titanium dioxide nanopattern by electron beam exposure is as follows: using electron beam exposure technology, a high-energy electron beam is bombarded on the sample surface. The electron beam scans according to the inverse structure of the set pattern, causing the PMMA photoresist of the inverse structure pattern to denature and thus solidify. Then, the undenatured and uncured PMMA photoresist is removed by developing solution, exposing the underlying titanium dioxide layer in the uncured PMMA photoresist area. In step 3, the titanium dioxide layer is vertically etched with an ion beam until the underlying silver film layer is exposed. At this point, only the partially etched titanium dioxide layer with a metallic aluminum mask remains on the surface. The specific process is as follows: First, the nanopattern is transferred onto the titanium dioxide layer through reactive ion etching. During the etching process, an etchant composed of SF6, CHF3, and O2 gas is used to etch chromium. Then, a plasma etching machine is used to etch titanium dioxide with aluminum as a hard mask, and an etchant composed of CCl4 and O2 gas is introduced during the process.

2. The method for fabricating high aspect ratio titanium dioxide nanopatterns on a silver substrate according to claim 1, characterized in that, The angle between the side face of the titanium dioxide nanopillar, the structural unit in the prepared titanium dioxide nanopattern, and the horizontal plane is between 80° and 90°.

3. The method for processing high aspect ratio titanium dioxide nanopatterns on a silver substrate according to claim 1, characterized in that, In step 2, after the photoresist is removed by the stripping solution, the photoresist is further removed and stripped by a pneumatic gun containing acetone.

4. The method for processing high aspect ratio titanium dioxide nanopatterns on a silver substrate according to claim 1, characterized in that, In step 4, the aspect ratio of the nanopattern is greater than 30. The aspect ratio of the titanium dioxide nanopillar refers to the ratio of the height of the titanium dioxide nanopillar to the minimum feature size. The nanopattern is a reflective metasurface or metalens with light-concentrating properties.

5. The method for processing high aspect ratio titanium dioxide nanopatterns on a silver substrate according to claim 1, characterized in that, The thickness H3 is controlled between 100-200 nm.

Citation Information

Patent Citations

  • Optical device structure unit of visible light wave band transform and optical device

    CN106054287A

  • Vertical etching process for preparing titanium dioxide with high longitudinal-to-width ratio

    CN110347014A

  • Body silicon MEMS and CMOS circuit integrating method capable of removing residual silicon

    CN1949477A